KEANEKARAGAMAN JENIS MANGROVE DI PANTAI MUTIARA DESA KOTA PARI KECAMATAN PANTAI CERMIN KABUPATEN SERDANG BEDAGAI PROVINSI SUMATERA UTARA - Sina sina; Retna Astuti Kuswardani; Jamilah Nasution (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
This Research on the diversity of Mangrove species in Pantai Mutiara Pari Village, Pantai Cermin Subdistrict, Serdang Bedagai Regency, North Sumatera Province was conducted in October s.d November 2012. The objective of this research is to know the diversity of species and mangrove vegetation based on growth level. The research method is explorative survey technique method. The sample collection for the research vegetation data consisted of observation plots with a total of 12 plots derived from 3 transects. The results of the study were 6 species of mangroves: Avicennia marina, Bruguiera sexangula, Rhizophora apiculata, Rhizophora stylosa, Rhizophora mucronata, and Nypa fruticans, belonging to 3 families namely Avicenniaceae, Rhizophoraceae, and Arecaceae. From the analysis, it is known that Avicennia marina, Rhizophora apiculata and Rhizophora stylosa species dominate the coastal area of Pantai Mutiara Desa Kota Pari Pantai Pantai Cermin. Based on the analysis of data obtained, the index of diversity (H ') of mangroves on the beach is low, ie the seedlings H' = 0.87, the H1 = 1,34 and the H '= 1.20. This indicates that the type of mangrove contained in the beach is small.